2020
DOI: 10.1364/osac.397603
|View full text |Cite
|
Sign up to set email alerts
|

Noise amplification in all-normal dispersion fiber supercontinuum generation and its impact on ultrafast photonics applications

Abstract: Highly coherent and low-noise supercontinuum (SC) sources based on nonlinear spectral broadening of femtosecond pulses in all-normal dispersion (ANDi) fibers are attractive for many applications in ultrafast photonics. By simulating a real nonlinear pulse compression experiment, we numerically investigate the impact of shot noise and technical pump laser fluctuations on the quality and stability of single-cycle pulse generation and other multi-shot experiments based on the manipulation of the SC spectral phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The superior coherence and noise properties of ANDi SCs over conventional SCs were verified, for example, by measurements of relative intensity noise (RIN), spectral coherence, dispersive Fourier transformation, and RF beating with stabilized laser diodes 45,51,65 . ANDi SC also possess a remarkable resistance against technical pump laser fluctuations 54,64,66 , while conventional SCs amplify such fluctuations by up to 20 dB, even in the regime where coherent dynamics dominate 62 . Describing incoherent nonlinear dynamics in terms of the MPR gain is therefore a successful concept for explaining the superior stability of ANDi SC.…”
Section: Noise Control By Dispersion Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior coherence and noise properties of ANDi SCs over conventional SCs were verified, for example, by measurements of relative intensity noise (RIN), spectral coherence, dispersive Fourier transformation, and RF beating with stabilized laser diodes 45,51,65 . ANDi SC also possess a remarkable resistance against technical pump laser fluctuations 54,64,66 , while conventional SCs amplify such fluctuations by up to 20 dB, even in the regime where coherent dynamics dominate 62 . Describing incoherent nonlinear dynamics in terms of the MPR gain is therefore a successful concept for explaining the superior stability of ANDi SC.…”
Section: Noise Control By Dispersion Engineeringmentioning
confidence: 99%
“…While our discussion has so far focused on intensity noise, nonlinear spectral broadening in the normal dispersion regime also has substantial advantages when phase noise or relative timing jitter (RTJ) between the spectral components is considered. ANDi SC generate new spectral components that are temporally synchronized to the pump pulse with RTJ in the order of only 100 attoseconds, while conventional SC exhibit up to 2 orders of magnitude larger fluctuations [52][53][54] . This is due to the coupling of amplitude and phase noise during soliton propagation in anomalous GVD, which is significantly reduced in SPM-dominated spectral broadening in normal GVD.…”
Section: Applications and Future Directionsmentioning
confidence: 99%
“…In addition to these limitations induced by different nonlinear effects, the impact of technical noise on ANDi SC generation, such as relative intensity noise (RIN) of the pump pulses at levels higher than the shot-noise limit, was the subject of several recent numerical and experimental studies [120][121][122][123], with seemingly contradictory results. While it was demonstrated that a pump laser RIN as low as 0.6% drastically degrades the coherence even for pump pulses as short as 100 fs [120], the RIN of the SC in the central part of the spectrum can actually be lower than the RIN of the pump laser itself [120,121].…”
Section: A All-normal Dispersion (Andi) Fibersmentioning
confidence: 99%
“…While it was demonstrated that a pump laser RIN as low as 0.6% drastically degrades the coherence even for pump pulses as short as 100 fs [120], the RIN of the SC in the central part of the spectrum can actually be lower than the RIN of the pump laser itself [120,121]. This result was unexpected but clearly explained by [122], where the authors determined that the amplitude noise is converted into timing jitter, which affects only the coherence and not the RIN of the SC. However, this timing jitter remains in the order of only 100 attoseconds for practical pump laser parameters, which is up to two orders of magnitude lower than the jitter introduced by conventional soliton-based SC [124,125], and therefore has little practical relevance for most applications.…”
Section: A All-normal Dispersion (Andi) Fibersmentioning
confidence: 99%
“…about an order of magnitude higher than the corresponding Er:fiber system This excess noise has recently been identified as the major performance limiting factor for the further development of high-power frequency comb sources at 2 µm [2].In this contribution I discuss the conditions required for suppressing this excess noise generation during nonlinear spectral broadening, present specialty optical fibers specifically designed for this purpose, and review the latest developments in their application aimed at realizing the next generation of ultra-low noise frequency combs and ultrashort pulse sources in the 2 µm spectral region. It is shown that ultra-low noise nonlinear spectral broadening and supercontinuum (SC) generation is enabled by all-normal dispersion (ANDi) fibers, which effectively suppress quantum and polarization noise amplification and lead to nonlinear dynamics that are extremely robust against technical noise [3,4]. The application of these ANDi SC sources for the coherent seeding of ultrafast Thulium-/ Holmium-doped fiber amplifiers is demonstrated to result in an order-of-magnitude reduction of RIN to < 0.05%, i.e.…”
mentioning
confidence: 99%